Origin–destination (OD) of the interprovincial floating population of China. Issue 1 (4th November 2016) - Ai, Tinghua; Zhou, Mengjie; Tian, Jing; Ye, Ning
ABSTRACT: China's large floating population catalyzes economic development, redistributes the population, and promotes social changes to the social structure, lifestyle patterns, and cultural values. The floating population is a unique group faced with numerous problems stemming from cultural and lifestyle differences. Understanding and visualizing the distributional characteristics and patterns of the floating population is crucial for developing effective social policies. In this study, the origin–destination (OD) map and its adjustment destination–origin (DO) map are used to represent the interprovincial floating population. The OD or DO map can be regarded as a two-level spatial treemap representing the floating population recorded by pairs of locations. In accordance with the different hierarchy of the two-level spatial treemap, the OD and DO are distinguished. The migration volume of the floating population data is represented by the OD and DO maps to find the population's direction of movement, magnitude, and hot-spots. The migration indicators including migration effectiveness, migration preference indexes, and sex ratios are represented by the OD and DO maps, which assist in to reviewing and studying the deep patterns of floating population.